Consumers' experiences and values in conventional and alternative medicine paradigms: a problem detection study (PDS) - Emmerton Lynne; Fejzic Jasmina; Tett Susan E (BMC, 2012)
Abstract Background This study explored consumer perceptions of complementary and alternative medicine (CAM) and relationships with CAM and conventional medicine practitioners. A problem detection study (PDS) was used. The qualitative component to develop the questionnaire used a CAM consumer focus group to explore conventional and CAM paradigms in healthcare. 32 key issues, seven main themes, informed the questionnaire (the quantitative PDS component - 36 statements explored using five-point Likert scales.) Results Of 300 questionnaires distributed (Brisbane, Australia), 83 consumers responded. Results indicated that consumers felt empowered by using CAM and they reported positive relationships with CAM practitioners. The perception was that CAM were used most effectively as long-term therapy (63% agreement), but that conventional medicines would be the best choice for emergency treatment (81% agreement). A majority (65%) reported that doctors appeared uncomfortable about consumers' visits to CAM practitioners. Most consumers (72%) believed that relationships with and between health practitioners could be enhanced by improved communication. It was agreed that information sharing between consumers and healthcare practitioners is important, and reported that "enough" information is shared between CAM practitioners and consumers. Consumers felt comfortable discussing their medicines with pharmacists, general practitioners and CAM practitioners, but felt most comfortable with their CAM practitioners. Conclusions This PDS has emphasized the perceived importance of open communication between consumers, CAM and conventional providers, and has exposed areas where CAM consumers perceive that issues exist across the CAM and conventional medicine paradigms. There is a lot of information which is perceived as not being shared at present and there are issues of discomfort and distrust which require resolution to develop concordant relationships in healthcare. Further research should be based on optimisation of information sharing, spanning both conventional and CAM fields of healthcare, due to both the relevance of concordance principles within CAM modalities and the widespread use of CAM by consumers.